Field Identification of Citrus Canker Symptoms and Decontamination Procedures - Mongi Zekri; Holly L. Chamberlain; Pete Timmer; Pamela D. Roberts; Rosa M. Muchovej (EDIS)
Citrus canker, caused by a bacterial pathogen Xanthomonas axonopodis pv. citri, is a serious disease of most citrus varieties. The disease causes necrotic lesions on leaves, stems, and fruit (Figure 1 and Figure 2). Severe infestation can cause defoliation, premature fruit drop, twig dieback, general tree decline, and very bad blemishes on fruit. Trees infected with citrus canker become weak, unproductive, and unprofitable. This document is PP-214, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date October 2005.